Grouping techniques in an EFL classroom - Marlene Ramírez Salas (Actualidades Investigativas en Educación)
This article focuses on the need for English language teachers to use group work as a means to foster communication among students.  The writer presents a definition of group work, its advantages and disadvantages, some activities for using group work and some grouping techniques created or adapted by the writer to illustrate the topic.